Discussion of Dr. Anderson's Case with a Focus on the Child's Use of the Analyst at Different Developmental Stages. Issue 1 (1st January 2020) - Rosenblitt, Donald
ABSTRACT: A review of some aspects of a child's use of the analytic process over a series of developmental phases with an emphasis upon the nature of the transferential relationship